Cultivating a giving-back culture: an investigation into the motivations of millennial donors - Hart, Sarah B. (Kansas State University, 2011)
Cultivating relationships with millennial donors -- individuals born between 1982 through 1995 -- has become a topic of interest for researchers, organizations and fundraisers. Kansas State University had begun creating a “giving-back culture” among current students through a student-led campaign, in the hope of augmenting alumni donations to the university in the future. This study explored current students’ motives to give back to their university, determined the factors influencing their decision-making process, and discerned the effects of a student-giving campaign on postgraduates’ giving behavior. Roger’s Diffusion of Innovations model helped explain the influence of communication channels and opinion leaders on the decision-making process of millennial donors, both alumni and current students. This study found that millennials are motivated to donate based on several campaign factors, such as the mission, how the money is be used, the receiving of a gift for their donation, and pride in the institution. Friends and close colleagues have a positive influence on millennials’ donation decisions. Millennials also were found to have a preference for the traditional medium of newspaper, along with a high degree of influence for campaign events with face-to-face communication. The lack of apparent effect for students’ self-reported preferences for social media seems to indicate that either diffusion is not at work for this campaign, or that the diffusion process has yet to accelerate for giving back. These findings support previous research on alumni-donor motivations as well as build a foundation for future studies on millennial-donor motivations.
Keywords: millennial donors; millennial donors motivations; K-State Proud; giving back; giving back culture; alumni donors; Mass Communications (0708)